Low Birth Weight, Renal Morphometry and Blood Pressure in Adolescent Females - Ninive Núñez López; Maira Pardo Rodríguez; Raquel Izquierdo de la Cruz; Jorge Bacallao Gallestey (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: nowadays, hypertension is a health problem directly causing disability and death. Epidemiological data suggest that pre- and postnatal nutrition can be an important factor in the etiopathogenesis of this disease. Objective: to evaluate the effects of low birth weight on blood pressure and kidney size in adolescent females. Methods: a cross-sectional study was conducted in 50 adolescent females from Marianao, Havana. The following variables were measured: weight, height, systolic and diastolic blood pressure, birth weight and length and body mass index. Kidney length, width, parenchyma and volume were measured by ultrasound. Results: differences in blood pressure related to weight and length at birth were nonsignificant. Renal variables did not show significant changes in the classification by birth weight. An important relationship between systolic blood pressure and two indicators of the relative kidney size was found. Conclusion: results did not show an association between low birth weight and high blood pressure. It is demonstrated that blood pressure values are positively related to body adiposity and small kidney size.